SISTEM PAKAR DIAGNOSIS CORONA VIRUS “ViroCHECK” MENGGUNAKAN ALGORITMA DECISION TREE - Lubis, Hendarman -; Temartenan, Jecklyn Shindy; Faizah, Safira (TRANSFORMASI, 2025)
The rapid spread of the virus, with symptoms ranging from mild to severe, makes early diagnosis and detection crucial in preventing and controlling the spread of this disease. Limited laboratory testing capacity, especially in areas with minimal healthcare facilities, requires a system capable of facilitating early identification based on symptoms and patient history, quickly, accurately, and efficiently. One approach is an expert system. The "ViroCheck" Coronavirus Diagnosis Expert System was developed using the Design Thinking Method. This expert system aims to assist users in diagnosing possible Coronavirus infection based on symptoms experienced. The decision-making process uses a Decision Tree algorithm, which is able to classify diagnostic results based on training data from previous cases. Problem analysis uses SWOT analysis, feasibility analysis uses TELOS analysis, and testing uses Usability Heuristic indicators that can observe user activity. The test results were 87%, proving that the designed digital startup has met user needs.Keywords: Expert System, Coronavirus, Decision Tree, Design Thinking, SWOT, TELOS, Usability Heuristic